2019
DOI: 10.1097/jnc.0000000000000015
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Interventions to Enhance PrEP Uptake Among Black Men Who Have Sex With Men

Abstract: In the United States, nearly 500,000 men who have sex with men (MSM) are at risk of contracting HIV. Men who have sex with men constitute 70% of all new cases of HIV in the United States; within this population, the incidence of HIV infection is the highest among Black MSM. Our integrated review synthesized published behavioral interventions designed to enhance the uptake of and adherence to pre-exposure prophylaxis (PrEP) for the prevention of HIV in the Black MSM population. A search of 4 electronic database… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 34 publications
(89 reference statements)
2
9
0
Order By: Relevance
“…7 Barriers to uptake include risk misperception by high risk groups, insufficient provider knowledge and willingness to prescribe PrEP, limited access to prevention health services disproportionally experienced by the most vulnerable groups, stigma and concern for side effects. [8][9][10] These barriers have limited the real world effectiveness of PrEP and additional PrEP options are needed to expand coverage among those who could most benefit from it.…”
Section: Introductionmentioning
confidence: 99%
“…7 Barriers to uptake include risk misperception by high risk groups, insufficient provider knowledge and willingness to prescribe PrEP, limited access to prevention health services disproportionally experienced by the most vulnerable groups, stigma and concern for side effects. [8][9][10] These barriers have limited the real world effectiveness of PrEP and additional PrEP options are needed to expand coverage among those who could most benefit from it.…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight the need for messaging about: relatively low side effects to ease concerns about PrEP, personal risk assessment and indications for PrEP, and PrEP clinics and assistance programs to help cover PrEP costs. 12,16,20,21,[64][65][66][67][68] Evidence of effective messaging through advertisement campaigns and social networks to enhance PrEP uptake has been encouraging and might be expanded to reach more MSM who need PrEP. 46,47 We found that insurance coverage and access were prominent reasons for never using PrEP among MSM who reported CAS.…”
Section: Use Of Prep Currently Previously and Nevermentioning
confidence: 99%
“…Positive associations were also found between essence of sex and PrEP conspiracy beliefs, as well as sexual freedom and PrEP conspiracy beliefs, which may also be explained by opposing discourses as described previously. Sex-positivity aligns with eudemonic discourse in which sexual pleasure and sexual freedom are centered (Lewis, 2004), whereas PrEP has primarily been aligned with risk/preventive discourse (Myers & Mayer, 2011;Remy & Enriquez, 2019;Reyniers et al, 2017;Young & McDaid, 2014;Calabrese & Underhill, 2015). PrEP uptake and sex-positivity may therefore be inherently at odds with one another: PrEP uptake signals the medicalization of sex and acknowledgment of oneself as a "subject of risk" who will participate in "socially unsanctioned sex," contradicting a sex-positive perspective (Race, 2016, pp.…”
Section: Discussionmentioning
confidence: 99%